«Giustizia mosse il mio alto fattore». Divine government of the world, legal order and the measure of punishment in Dante’s Comedìa - González de León Berini, Arturo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
With unparalleled literary beauty, the Comedìa reflects the Catholic worldview that formed the backbone of medieval Christianity, whose greatest philosophical and theological exponent was saint Thomas. Throughout the entire itinerary, we see the imprint of Aquinas present at the very heart of the poem. Here I will analyze how the fundamental theological question of the divine government of the world permeates the entire Comedìa, both in its formal structure and in certain concrete aspects of Dante’s journey. From that premise, I will study the consequences of the abovesaid on that juridical order reflected in the «architecture» of the Inferno, whose lintel is so eloquent: «Giustizia mosse il mio alto fattore; / fecemi la divina podestate, / la somma sapienza e ‘l primo amore». Finally, I will focus on the proportionality of punishments suffered by the condemned, as an indicator of the natural measure of decisions made by divine justice.